The first epistle of Paul to the Corinthians : an introduction and commentary - Morris, Leon Lamb, 1914-2006 (Leicester, UK IVP, 1985)
Includes bibliographical references.
Keywords: Bible. N.T. Corinthians, 1st -- commentaries